Lubrication Performance Analysis of RV Reducer Cycloid Tooth Profile Modification - Jun Wang; Zhilong Chen; Qunchao Chen; Wentao Li; Quan Wang; Daxing Zhao (Jixie chuandong)
With the consideration of the thermal effect and piezo-viscous characteristic of lubricants， the numerical model of line contact elastohydrodynamic grease lubrication between cycloid gear and pin wheel is established， and the fully numerical solution of the model is obtained and the grease film pressure distribution， grease film temperature rising distribution and the grease film shape of are obtained. Combined with the profile of the cycloidal wheel， the effect of the tooth profile modification schemes and the modification quantity on grease film pressure， grease film shape， grease film temperature rising and friction power loss are analyzed. The results indicate that as the radial clearance between the modified tooth profile and the theoretical tooth profile increases， the friction loss power increases， and the minimum grease film thickness increases first and then decreases. Under the condition of the same radial clearance between the modified tooth profile and the theoretical tooth profile， the lubrication performance of the anti-bow profile modification is better that the positive equidistant modification with positive radial-moving modification. The negative equidistant modification with negative radial-moving modification has the worst lubrication performance. This study provides a new method for tooth profile modification of the cycloidal gear of the RV reducer by considering lubricity.